ANALISIS NILAI TAMBAH DAUN KELOR (MORINGA OLEIFERA) PADA INDUSTRI PT MASPETE ORGANIK KUFEU KABUPATEN MALAKA (Studi kasus: kelompok Maspete) - Garvasilus Kopong Laga; Umbu Joka; Ahmad Subchiandi Maulana (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
PT Maspete Organik Kufeu is an industry that implements organic farming patterns for moringa plant commodities that are managed organically. This study aims to determine the benefits obtained from processing Moringa Leaves into Moringa Tisan in the PT Maspete Organik Kufeu industry and to analyze the amount of added value of Moringa Tisan in the PT Maspete Organik Kufeu industry. The type of research used in this study is a case study with a quantitative descriptive approach. The results of the study show that: 1). The total cost incurred in one production process is IDR 3,125,000.00, the amount of income obtained in one month of production is IDR 5,100,000.00 and the amount of income obtained is IDR 1,975,000.00. 2). The added value of Moringa leaves into Moringa leaf Tisan in one production is 51.02% (high category) while the labor margin is 15.62%, the margin for other input contributions is 44.95% and the entrepreneur's profit margin is 39.43% which means that the margin for labor profits is smaller than the entrepreneur's profit margin and other input contributions.